2023
DOI: 10.17582/journal.pjz/20190922190944
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Preferences of Wild Mammalian Species around River Chenab in Sialkot, Gujrat and Gujranwala Districts, Punjab, Pakistan

Abstract: Authors' Contribution ED contributed to the conception and design of the study, data collection, statistical analysis, interpretation of data and drafting the manuscript. HS contributed data collection, statistical analysis and interpretation of data. SD and HH were involved in conception and design of study, and critical revision of manuscript. All authors have read and approved the finalized manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…to April 2021 indicated that it was less diverse, and birds were less evenly distributed than in the research of Tehsil Sahiwal, with H=2.145 and E=0.3882, respectively. A total of 22 species were reported from Gujranwala (Altaf, 2021). A study counducted in the rural and urban areas of Sargodha from October 2015 to September 2016 revealed a total of 3057 birds from both areas with Shannon diversity (2.444), richness (4.112) and evenness (0.3387).…”
Section: Discussionmentioning
confidence: 99%
“…to April 2021 indicated that it was less diverse, and birds were less evenly distributed than in the research of Tehsil Sahiwal, with H=2.145 and E=0.3882, respectively. A total of 22 species were reported from Gujranwala (Altaf, 2021). A study counducted in the rural and urban areas of Sargodha from October 2015 to September 2016 revealed a total of 3057 birds from both areas with Shannon diversity (2.444), richness (4.112) and evenness (0.3387).…”
Section: Discussionmentioning
confidence: 99%
“…Their existence is essential to many ecosystems and greatly enhances sustainability. Furthermore, a variety of mammalian species are bene cial for nutrition, providing important sources of protein for human diets (Altaf et al, 2023). In Pakistan, peri-urban areas are the preferred habitat for northern palm squirrels (Funambulus pennantii) (Altaf et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a variety of mammalian species are bene cial for nutrition, providing important sources of protein for human diets (Altaf et al, 2023). In Pakistan, peri-urban areas are the preferred habitat for northern palm squirrels (Funambulus pennantii) (Altaf et al, 2012). The habitats around agricultural areas are preferred by (Hystrix indica) Indian crested porcupine (Safeer et al, 2018), (Sus scrofa) Indian wild boar (Chughtai et al, 2018), and (Herpestes javanicus) small Indian mongoose (Altaf, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deserts contain scarcity of surface water which directly affects species richness because just like other organisms, water is the basic requirement for the survival of birds [8]. The total number of bird species across the globe is 9042 while 2700 avian species have been reported from Asia [9]. Pakistan harbours a diverse avian fauna due to its geographical structure that encompasses diversity of habitat, i.e., forest habitat, desert habitat, and aquatic habitat, and is home to more than 750 species of birds including 105 water bird species [10].…”
Section: Introductionmentioning
confidence: 99%